2020
DOI: 10.11591/ijece.v10i5.pp4623-4630
|View full text |Cite
|
Sign up to set email alerts
|

28 GHz balanced pHEMT VCO with low phase noise and high output power performance for 5G mm-Wave systems

Abstract: This paper presents the study and design of a balanced voltage controlled oscillator VCO for 5G wireless communication systems. This circuit is designed in monolithic microwave integrated circuit (MMIC) technology using PH15 process from UMS foundry. The VCO ensures an adequate tuning range by a single-ended pHEMT varactors configuration. The simulation results show that this circuit delivers a sinusoidal signal of output power around 9 dBm with a second harmonic rejection between 25.87 and 33.83 dB, the oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The architecture of the proposed VCO is based on the Colpitts structure studied in the references [16][17][18] and the structure proposed by the authors in [12] as shown in Figure 2. The active part of this oscillator consists of two transistors pHEMT 1 and pHEMT 2: each one has 4 fingers and a gate length and width of 0.25 µm and 20 µm, respectively.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%
See 3 more Smart Citations
“…The architecture of the proposed VCO is based on the Colpitts structure studied in the references [16][17][18] and the structure proposed by the authors in [12] as shown in Figure 2. The active part of this oscillator consists of two transistors pHEMT 1 and pHEMT 2: each one has 4 fingers and a gate length and width of 0.25 µm and 20 µm, respectively.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%
“…The chip includes the oscillator circuit, RF access pad and three bias pads. While the chip size of the circuits presented in [8,12,15] are 3.75 mm 2 , 0.515 mm 2 and 0.5 mm 2 respectively. It is therefore a compact and reduced structure, compared to the structures published, recently, in the literature.…”
Section: Voltage Controlled Oscillator Circuitmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the total power consumption for the oscillator is 70 mW. In [76], the power consumption of voltage controlled oscillator is 122 mW. It is measured under phase noise at the oscillation frequency varies from 26.46 to 28.90 GHz.…”
Section: Model Of Power Consumptionmentioning
confidence: 99%